What will it take to observe processes in 'real time'? - Leone, Stephen R.; McCurdy, C. William; Burgdörfer, Joachim; Cederbaum, Lorenz S.; Chang, Zenghu; Dudovich, Nirit; Feist, Johannes; Greene, Chris H.; Ivanov, Mikhail; Kienberger, Reinhard; Keller, Ursula; Kling, Matthias; et al. (Nature photonics, 2014)
Even for simple systems, the interpretations of new attosecond measurements are complicated and provide only a glimpse of their potential. Nonetheless, the lasting impact will be the revelation of how short-time dynamics can determine the electronic properties of more complex systems.
Gesehen am 21.09.2020